Escritas do eu em Ana Cristina César: uma pseudoautobiografia - Freitas, Mariana Nunes de (2014)
Heloisa Buarque de Hollanda, in her book 26 poetas hoje, gathered in this anthology the most talented poets of the 1970 s generation or mimeograph generation. Among artists like Cacaso, Francisco Alvim, Roberto Piva, Torquato Neto, Chacal and Roberto Schwarz, stands out Ana Cristina César (1952), a controversial figure who, after having committed suicide in 1983, had her genius recognized in the academic and artistic world. This tragic death is a privileged subject by the critics that, in general, explain the subjective characteristic of Ana C. s production through (auto) biographical traits, like trips, career, readings, affective relationships and even sexual orientation. However, the scholar Flora Süssekind in the book Até segunda ordem não me risque nada: os cadernos, rascunhos e a poesia-em-vozes de Ana Cristina César, adopts a more \"balanced\" posture between \"biographical, far too biographical\" and \"literary, only literary\" in which she risks a critical approach of this poet s writing. Thus, this Master\'s thesis is presented in order to analyze the poetry of Ana C. under the bias of literary criticism and not only in the biographical perspective; the proposal is, however, to analyze how Ana C. elaborates her literature so unique and with a very intimist diction. According to Maria Lucia de Barros Camargo in Atrás dos olhos pardos, the poet s writing subverts the female gender, while inscribed on her poetic a Pessoan subject, which only pretends to make confessions, even though it announces intimate statements. Therefore, it is seen that, while writing diaries, letters and texts of subjective nature, the subject of Ana C. s poetic does not show itself to the reader, does not manifest its intimacy, far less make revelations; which grants the texts made by the poet a character of pseudo-autobiography term initially used by Eneida Maria de Souza and borrowed to support the defense of this forged intimacy elaborated in Ana C. s lyric. To do so, the theories related to self-writing were of great value, some major authors were studied as, for example, Maurice Blanchot, Diana Klinger, Paul de Man, Clara Rocha, Eneida Maria de Souza, Philippe Lejeune, Leonor Arfuch, Luiz Costa Lima and Dominique Combe. Since the pseudo-autobiography, central defense of this dissertation, is perceived, mostly, in the deconstruction of the female genders of intimacy, were selected for study the diaries, letters, poetic self-portraits written by Ana Cristina César withdrawn mainly from the work A teus pés.